Motivacija za učenje in samopodoba - Lebarič, Nada (Psihološka obzorja (Ljubljana), 2002)
In this article we analyse motivation for learning. In the sample was included287 students fourth grade of Slovenian upper secondary schools. Our main questions were focused on the relationships between students motivation and their self-concept on the one side and on differences between students motivational factors on the other side. In further we analyse relations between learning success and motivation. The results of ours research show, that the self concept, in particular its academic self-concept, is significantly correlated with motivational factors. The particular part (dimension) of academic self-concept is students self-perception about their own abilities for learning and it is in relation with individuals value system. That can be seen when we observed students attitudes to acquire knowledge. Academic self-concept is basic factor for development and for the selection of learning strategies and it has the role of motivational factor.On the other side in academic self-concept are included very different abilities, what is helping students not only for better understanding in the processes of acquiring knowledge, but also for more qualitative production of new knowledge from acquiring information's. Our results show that obtain differences between students in motivation for learning and that higher learning success is in correlation with higher levelof motivation.
Keywords: motivacija; motivation; learning; učenje; uspešnost; samopodoba; psihologija; psychology; mladostniki